El último patriota de 1887 - Todd, Roberto H. (My University, 2014)
Artículo sobre la Asamblea Autonomista
Keywords: Baldorioty de Castro, Román, 1822-1889; Carbonell, Celedonio; Corchado, Martín J.; Montalvo, José; Cepeda, Francisco; Blanco Sosa, Julián E., 1830-1905; Guerra, Mauricio; Porrata Doria, Luis, 1845-1925